Enhanced data on Stolephorus grandis and Stolephorus waitei (Teleostei: Clupeiformes: Engraulidae), two species endemic to the Sahul Shelf, western Pacific Ocean - Hata, Harutaka; Wibowo, Kunto; Lavoué, Sébastien; Pogonoski, John J.; Appleyard, Sharon A.; Motomura, Hiroyuki (Zootaxa, 2024)
Eighteen and 23 specimens of two species of the poorly known anchovies Stolephorus grandis Hata & Motomura, 2021b and Stolephorus waitei Jordan & Seale, 1926 (Clupeiformes: Engraulidae), respectively, are examined. This study presents their detailed morphological characters including fresh colorations along with their precise distributional ranges within the Sahul Shelf coastal region. The “barcode” regions of the mitochondrial cytochrome c oxidase subunit I (COI) gene were examined in four specimens of S. waitei and one specimen of S. grandis. Both species diverged by 10.6% and > 10.3% mean (uncorrected) genetic distances from each other and from any other species of Stolephorus, respectively. Stolephorus waitei, S. grandis, and Stolephorus nelsoni Wongratana, 1987 form a monophyletic group of species endemic to the Sahul Shelf region. Additionally, the role and evolution of double lines on the dorsum observed in several species of Stolephorus, including S. grandis, are discussed.